Epidemiological and clinical features of laboratory-diagnosed severe fever with thrombocytopenia syndrome in China, 2011–17: a prospective observational study. Issue 10 (October 2018) - Li, Hao; Lu, Qing-Bin; Xing, Bo; Zhang, Shao-Fei; Liu, Kun; Du, Juan; Li, Xiao-Kun; Cui, Ning; Yang, Zhen-Dong; Wang, Li-Yuan; Hu, Jian-Gong; Cao, Wu-Chun; et al.
Summary: Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with an increasing case number and extensive geographical expansion, raising concerns locally and globally; however, the description of its clinical features needs to be addressed by large studies. We aimed to determine all the clinical features of SFTS in a large population of patients in an endemic area. Methods: In this prospective observational study, data were collected on patients admitted to the People's Liberation Army Hospital in Xinyang, Henan Province, China, with laboratory-diagnosed SFTS. Demographic, clinical, laboratory, and treatment data were collected for each patient, and patients were followed up within 2 weeks after discharge or discontinuation of treatment. The association between each demographic, clinical, and laboratory variable with a fatal outcome was assessed. A clinical scoring model was designed for the early prediction of a fatal outcome, and the effect of treatment on outcome was analysed. Findings: Between April 1, 2011, and Oct 31, 2017, 2096 patients with laboratory-confirmed SFTS were admitted. Mean age at admission was 61·4 years (SD 12·2) and 1239 (59%) patients were female. The case fatality rate (CFR) was 16·2% (95% CI 14·6–17·8). A higher risk was associated with being male (unadjusted odds ratio [OR] 1·45, 95% CI 1·15–1·83; p=0·002), older age (for a 10-year increase, unadjusted OR 1·82, 95% CI 1·62–2·04; p<0·0001), longer delay in admission (for every extra day taken before admission to hospital, unadjusted OR 1·18, 1·12–1·24; p<0·0001), presence of diarrhoea (adjusted OR 1·44, 1·12–1·87; p=0·005) or dyspnoea (adjusted OR 8·35, 5·97–11·69; p<0·0001), and development of haemorrhagic signs (adjusted OR 2·79, 95% CI 2·18–3·57; p<0·0001) or neurological symptoms (adjusted OR 30·26, 21·39–42·81; p<0·0001). Laboratory variables that were associated with death included abnormal concentrations of lactate dehydrogenase, aspartate aminotransferase, and blood urea nitrogen, and abnormal neutrophil percentage, which together with age and neurological symptoms were combined in the clinical scoring system. A total score of more than 8 was the optimal threshold to predict risk of death for patients who were evaluated within 6 days after symptom onset (area under the curve 0·879, 95% CI 0·855–0·902). For all participants, viraemia was a strong predictor of fatal outcome (all p<0·0001). Ribavirin therapy was effective in reducing CFR from 6·25% (15 of 240 participants) to 1·16% (two of 173 participants), but only in patients with a viral load below 1×10 6 copies per mL (hazard ratio 9·72, 95% CI 1·30–72·87; p=0·027). Interpretation: The changing epidemiological features and high CFR of SFTS underscore the necessity of continued surveillance. Early prediction of fatal outcome can be attained by monitoring of clinical and laboratory data. Ribavirin should be applied early, with best results achieved before the viral load reaches 1 × 10 6 copies per mL. Funding: National Natural Science Foundation of China.